2009
DOI: 10.2174/156802609789044407
|View full text |Cite
|
Sign up to set email alerts
|

IRAK-4 Inhibitors for Inflammation

Abstract: Interleukin-1 receptor-associated kinases (IRAKs) are key components in the signal transduction pathways utilized by interleukin-1 receptor (IL-1R), interleukin-18 receptor (IL-18R), and Toll-like receptors (TLRs). Out of four members in the mammalian IRAK family, IRAK-4 is considered to be the “master IRAK”, the only family member indispensable for IL-1R/TLR signaling. In humans, mutations resulting in IRAK-4 deficiency have been linked to susceptibility to bacterial infections, especially recurrent pyogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
99
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(107 citation statements)
references
References 71 publications
(115 reference statements)
2
99
0
1
Order By: Relevance
“…[11][12][13] Thus, activation of MAPK p38, ERK p44erk-1 and p42erk-2 by IL-18 was detected in a human NK cell line in previous studies. [14][15][16][17] However, little is known of the secretion and regulation of IL-18 in MM cells. In this study, we found that LPS induced IL-18 secretion and activated MAPK and NFκB signaling in MM.1S and ARP-1 cells simultaneously.…”
Section: Hmcl Primary Myeloma Cells DC and Culture Mediummentioning
confidence: 99%
“…[11][12][13] Thus, activation of MAPK p38, ERK p44erk-1 and p42erk-2 by IL-18 was detected in a human NK cell line in previous studies. [14][15][16][17] However, little is known of the secretion and regulation of IL-18 in MM cells. In this study, we found that LPS induced IL-18 secretion and activated MAPK and NFκB signaling in MM.1S and ARP-1 cells simultaneously.…”
Section: Hmcl Primary Myeloma Cells DC and Culture Mediummentioning
confidence: 99%
“…Recruitment of IRAK4 and IRAK1 to the MyD88-signaling complex elaborates NF-kB-dependent inflammation (2,3). MyD88 is also coupled to IFN regulatory factors (IRFs) that mediate differential expression of specific cytokines, depending on the TLR/IL-1R signaling pathway (4,5).…”
mentioning
confidence: 99%
“…It is clear that although similarities in IRAK4 activity exist between human and mouse, there are important differences as well. Mice deficient for IRAK4 are severely impaired in their cellular responses to IL-1, IL-18, and most TLR ligands, sharing an overlapping phenotype with IRAK4-deficient human patients (3). However, although IRAK4-deficient mice display broad susceptibility to viral and bacterial infections, IRAK4-deficient human patients exhibit a narrow infectious phenotype, limited primarily to pyogenic bacterial infections at an early age (6,7).…”
mentioning
confidence: 99%
“…Furthermore, the data presented here also warrant the inclusion of IRAK2 rs35060588 in future genetic association studies and the exploration of its functional phenotype in human carriers. IRAK inhibitors are already under development for the treatment of inflammation and B cell malignancies (6,35). In a dawning age of individualized medicine and straightforward sequence acquisition, broader studies into the genetic predisposition of infectious, autoimmune, and malignant diseases will help to characterize the potential value of rs35060588 and potentially other IRAK2 variants as biomarkers of disease or points of therapeutic intervention (e.g.…”
Section: Discussionmentioning
confidence: 99%